Interfaces sócio-espaciais no MST: refletindo a partir das contradições - Alice Rennó Werner Soares (2021)
This master's research was motivated by the dissatisfaction with the tendency in reproducing conventional projects processes in the architecture and urbanism field, even when there is a socio-spatial transformational intention, whether in the institutional participative processes, in the technical assistance or in the technical advisory. Having a MST group in a participative public hearing drew attention due to the articulation ability from its representatives, that even in such institutional environment which did not indeed stimulate their participation, managed to effectively engage and transmit their demands, in such way that those were included on the planning proposal from their home town. This has triggered interest for the emancipating and mobilizing bias on the educational background that take place at the MST schools, which amongst other things seems to reverberate on its members, in general. I had the opportunity to get closer to the socio-spatial group from Elisabeth Teixera’s school, in the Pátria Livre camp in São João de Bicas, a metropolitan region from Belo Horizonte. In this context, starting from spatial demands coming from the school’s management, I started an action research, with the objective of articulating a socio-spatial mobilization process from the students through interfaces, and not only answer the demands from students and dwellers. During this experience, I observed that, even being a group committed on fighting for their lands, some contradictions – especially on space production – coming from a capitalist mode of production, seem to be a trammel to the emancipating horizon, which is considered to be the main objective from the school and the camp. From this finding, and also due to the fact that all field work has been halted due the Covid-10 pandemic, the research turned its attention to the specificities from the production of the school spaces’, aiming to understand its contradictions. To present this research process, this thesis brings narratives from the practical experiences, both from the urban planning institutional context and from the MST’s Elisabeth Teixeira school context, and also the discussion on the contradictions observed in those environments, analyzed based on the mobilized theory. The objective of this thesis is to inform about the technical advisory practices in the architecture and urbanism scope in contexts similar to the MST camps, using interfaces to promote a problematization dialogue environment, avoiding assistance measures and heteronomous problem solving means.